Vitreous levels of vascular endothelial growth factor in eyes with anterior hyaloidal fibrovascular proliferation - Takaki Kobayashi (Dove Medical Press, 2010)
Takaki Kobayashi, Shigeki Machida, Takamitsu Fujiwara, Tadashi Ishibe, Daijiro KurosakaDepartment of Ophthalmology, Iwate Medical University School of Medicine, Iwate, JapanPurpose: To determine the intravitreal levels of vascular endothelial growth factor (VEGF) in eyes with anterior hyaloidal fibrovascular proliferation (AHFVP).Methods: Three eyes of three patients who underwent vitrectomy for proliferative diabetic retinopathy (PDR) and subsequently developed an AHFVP (AHFVP group) were studied. We measured the level of VEGF in vitreous samples collected at the primary and following operations by enzyme-linked immunosorbent assay. The vitreous levels of VEGF in 25 eyes of 22 patients with PDR were also studied as controls (PDR group).Results: The averaged VEGF level in the samples collected at the primary surgery was 1.98 ± 2.23 ng/mL in the PDR group, and it was 9.07, 1.94, and 8.07 ng/mL in the AHFVP cases. After the primary surgery, the VEGF level rose up to 49.50, 15.60, and 50.60 ng/mL at the subsequent surgeries for respective cases of the AHFVP group. These levels of VEGF were more than five times higher than the baseline at the primary surgery.Conclusion: The subsequent increase of the VEGF level after the primary surgery in eyes with an AHFVP suggests that the vitreous levels of VEGF are associated with the development of the AHFVP although only three eyes were studied.Keywords: VEGF, AHFVP, diabetic retinopathy